2018
DOI: 10.1021/acsanm.8b00409
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Organic Nanoparticles Constructed by a Facile “Self-Isolation Enhanced Emission” Strategy for Cell Imaging

Abstract: To achieve the highly emissive features and overcome the troublesome photobleaching for fluorescent organic molecules, a facile and versatile strategy named “self-isolation enhanced emission (SIEE)” was developed to prevent the π–π stacking of organic fluorophores by linking alkyl chains on their conjugated backbones. As a proof-of-concept, one or two octyl groups were grafted onto the backbone of 4,7-di­(thiophen-2-yl)­benzo­[c]­[1,2,5]­thiadiazole (termed as DTBT-0), resulting in two different molecules, ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…[27][28][29][30][31] By using these highly emissive AIEgens, dual-state emission can be easily achieved and they have potential real-world applications, [32][33][34] such as in PA detection and LFP visualization. Recently,f lexible alkyl chains were introduced into conventionalf luorescent molecules to prevent close packing of their core structures as well as strong p-p intermolecular stacking interactions, [35][36][37] thereby openingr adiative channels to afford highlye missive features in aggregates.T herefore, based on these considera-tions, to achieve ah ighly efficient dual-state emission platform for PA detection and LFP visualization,i nt his work, flexible alkyl chains were facilelya ttached to the commercial organic dye 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA)t o afford the tetraalkyl 3,4,9,10-perylenetetracarboxylate target compounds PTCA-C4, PTCA-C6, and PTCA-C12 (fort he structures, see Figure 1). As we anticipated, impressive fluorescence characteristics with photoluminescence quantum yields (PLQYs) of up to 95.0, 96.9, and 93.2 %w ereo btained for PTCA-C4, PTCA-C6, and PTCA-C12 in THF solution, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31] By using these highly emissive AIEgens, dual-state emission can be easily achieved and they have potential real-world applications, [32][33][34] such as in PA detection and LFP visualization. Recently,f lexible alkyl chains were introduced into conventionalf luorescent molecules to prevent close packing of their core structures as well as strong p-p intermolecular stacking interactions, [35][36][37] thereby openingr adiative channels to afford highlye missive features in aggregates.T herefore, based on these considera-tions, to achieve ah ighly efficient dual-state emission platform for PA detection and LFP visualization,i nt his work, flexible alkyl chains were facilelya ttached to the commercial organic dye 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA)t o afford the tetraalkyl 3,4,9,10-perylenetetracarboxylate target compounds PTCA-C4, PTCA-C6, and PTCA-C12 (fort he structures, see Figure 1). As we anticipated, impressive fluorescence characteristics with photoluminescence quantum yields (PLQYs) of up to 95.0, 96.9, and 93.2 %w ereo btained for PTCA-C4, PTCA-C6, and PTCA-C12 in THF solution, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the notoriousA CQ effect in OLMs, Tang et al proposedt he concept of "aggregation-induced emission'' (AIE) in 2001 and then developed tremendous AIE luminogens (AIEgens), which are usually non-or weakly emissive in dilute solution, buta re intensely emissive in the aggregated states ( Figure 1). [23] This developed SIEE method through alkyl chains could also provide the possibility to successfully obtain dual-state emission for OLMs ( Figure 1). Schematic diagrams of chemical structuresf or typical OLMs (ACQ, AIE, and SIEE) and their corresponding emission photographs in THF solution or aggregated states (with aw ater fraction of 0, 50, and 99 %, respectively) and in solid state.…”
Section: Introductionmentioning
confidence: 99%
“…nescent performance in aggregated states. [23] This developed SIEE method through alkyl chains could also provide the possibility to successfully obtain dual-state emission for OLMs ( Figure 1). Furthermore, it is interesting to note that, if the alkyl chains in conjugated molecules are proper constructed to preventt he strong p-p stacking in aggregateds tates, [24] a smart change from ACQ molecules to AIE molecules through the SIEE strategy coulda lso occur,w hich indicates the great role of the SIEE methodn ot only in fundamental understanding, but also in practical application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the large number of studies reported for nanomaterials based on metals, polymers, quantum dots, and carbon dots, [16,18–22] nanoparticles (NPs) based on organic fluorophores have been rarely reported due to aggregation‐caused quenching (ACQ) in the condensed phase, which has been observed for most conventional fluorophores possessing an aromatic system with high planarity [23–24] . For biomedical imaging, the development of FONs with high brightness in water is critical [25–28] . Up to now, FONs with a controlled morphology and tunable emission have been rarely developed [29–31] …”
Section: Introductionmentioning
confidence: 99%